Banana Plant Nutrient Deficiencies Identification using Deep Learning - Kadipa Aung Myo Han; Noppadol Maneerat; Kasemsuk Sepsirisuk; Kazuhiko Hamamoto (My University, 2023)
This paper presents nutrient deficiency multi-class classification in banana plant data sets using a deep convolutional neural network. In this paper, healthy and eight nutrient deficiency classes were studied. The performance was evaluated in different situations of two public data sets. The proposed method can provide sensitivity and specificity in Raw Images, Raw Images with combination, Augmented Images, and Augmented Images with the combination. Furthermore, nearly 88% of the F1-score was outperformed.
Keywords: Smart Agriculture and AI; Banana Cultivation and Research